PHYTOCHEMICAL SCREENING AND TOXICITY TEST OF MANGROVE LEAF ETHANOL EXTRACT (Bruguiera gymnorrhiza) WITH BRINE SHRIMP LETHALITY TEST (BSLT) METHOD - Friyan Criscanus Manopo; Fatimawali Fatimawali; Olvie Datu (UNIVERSITAS SAM RATULANGI, 2023)
Cancer is one of the biggest causes of death in the world. Therefore, efforts to manufacture drugs for cancer treatment continue to be developed. One of the efforts to develop cancer drugs is by using medicinal plants which are empirically used by local communities in various regions. This study aims to analyze the content of secondary metabolites contained in the leaf extract of the Mangrove Bruguiera gymnorrhiza and to determine the potential as an anticancer by determining the LC50 value. The extract was obtained by maceration using 96% ethanol solvent, identification of secondary metabolites by phytochemical screening and to determine the anticancer potential using the BSLT method with data analysis using Microsoft Excel. The phytochemical test results showed that the leaf extract contained alkaloids, flavonoids, saponins, tannins, and did not contain steroid/triterpenoid compounds. The results of the analysis showed that the ethanol extract of mangrove leaf (Bruguiera gymnorrhiza) was highly toxic with an LC50 value of 24.1 Âµg/ml.Â